A Web-Based Sexual Violence Bystander Intervention for Male College Students: Randomized Controlled Trial - Salazar, Laura F; Vivolo-Kantor, Alana; Hardin, James; Berkowitz, Alan (JMIR Publications, 2014)
BackgroundBystander intervention approaches offer promise for reducing rates of sexual violence on college campuses. Most interventions are in-person small-group formats, which limit their reach and reduce their overall public health impact. ObjectiveThis study evaluated the efficacy of RealConsent, a Web-based bystander approach to sexual violence prevention, in enhancing prosocial intervening behaviors and preventing sexual violence perpetration. MethodsA random probability sample of 743 male undergraduate students (aged 18 to 24 years) attending a large, urban university located in the southeastern United States was recruited online and randomized to either RealConsent (n=376) or a Web-based general health promotion program (n=367). Participants were surveyed online at baseline, postintervention, and 6-months postintervention. RealConsent was delivered via a password-protected Web portal that contained six 30-minute media-based and interactive modules covering knowledge of informed consent, communication skills regarding sex, the role of alcohol and male socialization in sexual violence, empathy for rape victims, and bystander education. Primary outcomes were self-reported prosocial intervening behaviors and sexual violence perpetration. Secondary outcomes were theoretical mediators (eg, knowledge, attitudes). ResultsAt 6-month follow-up RealConsent participants intervened more often (P=.04) and engaged in less sexual violence perpetration (P=.04) compared to controls. In addition, RealConsent participants reported greater legal knowledge of sexual assault (P<.001), greater knowledge of effective consent (P<.001), less rape myths (P<.001), greater empathy for rape victims (P<.001), less negative date rape attitudes (P<.001), less hostility toward women (P=.01), greater intentions to intervene (P=.04), less hyper-gender ideology (P<.001), less positive outcome expectancies for nonconsensual sex (P=.03), more positive outcome expectancies for intervening (P<.001), and less comfort with other men's inappropriate behaviors (P<.001). ConclusionsOur results support the efficacy of RealConsent. Due to its Web-based format, RealConsent has potential for broad-based dissemination thereby increasing its overall public health impact on sexual violence. Trial RegistrationClinicaltrials.gov: NCT01903876; http://clinicaltrials.gov/show/NCT01903876 (Archived by WebCite at http://www.webcitation.org/6S1PXxWKt).